Alteration of the P-wave non-linear dynamics near the onset of paroxysmal atrial fibrillation. Issue 7 (July 2015) - Martínez, Arturo; Abásolo, Daniel; Alcaraz, Raúl; Rieta, José J.
Highlights Non-linear dynamics in the P-wave progression before the onset of PAF is quantified by CTM. The onset of PAF is predicted at least with a time in advance of 2 h. Linear and non-linear dynamics coexist in the disturbed atrial depolarization preceding PAF.